The icon of Ukrainian Nazis: on the question of the historical assessment of the «heroes» under the Protection of the Virgin Mary and their modern admirers - A. V. Sushko (Омский научный вестник: Серия "Общество. История. Современность")
The study is based on a source analysis (external criticism) of a modern icon of Ukrainian nationalists, on which, under the Protection of the Virgin Mary, among other historical figures, Greek Catholic metropolitans Andrei Sheptytsky and Joseph Slipyi are depicted, as well as the leaders of the OUN-UPA (organizations recognized as extremist in Russia and banned) Stepan Bandera and Roman Shukhevych. A historical assessment of the activities and the presence of these figures who collaborated with the German Nazis on the icon is given. The main emphasis is on the interaction of the depicted «heroes» with the NSDAP, SS, SD and Gestapo, found guilty of crimes against humanity by the International Military Tribunal. In addition to the image itself, which became the reason for writing this article, the source for the study is the forensic investigative documentation of the Soviet state security agencies, during and after the end of the Great Patriotic War, interrogating captured employees of the German special services, Ukrainian nationalists and witnesses to their war crimes. The presence of specific common features in the biographies depicted on the icon of Nazi criminals has been established. The author emphasizes that people who publicly glorify Ukrainian nationalists through an icon are subject to Article 4 of the International Convention on the Elimination of All Forms of Racial Discrimination, which requires states parties to the Convention to prosecute them.